Scents modulate anxiety levels, but electroencephalographic and electrocardiographic assessments could diverge from subjective reports: a pilot study - Morozova, Marina; Gabrielyan, Irina; Kleeva, Daria; Efimova, Victoria; Lebedev, Mikhail (Frontiers in Behavioral Neuroscience, 2025)
Scents can influence anxiety, including that experienced in clinical environments. This study examined the effects of two distinct aromas: lavender, a fragrance widely recognized for its calming properties, and African stone, a musky and relatively unfamiliar scent. Twenty healthy participants underwent alternating periods of rest and scent inhalation in a dental office environment while anxiety was assessed using the State–Trait Anxiety Inventory (STAI), electroencephalographic (EEG) measures of theta, alpha, and beta power ratios, and electrocardiographic (ECG) measures of heart rate variability (HRV). Lavender inhalation significantly reduced self-reported state anxiety scores but did not produce measurable changes in EEG or HRV indices, possibly due to the short (5 min) exposure duration. African stone, in contrast, did not alter self-reported anxiety but induced significant physiological effects, including reduced theta and, increased alpha power in parieto-occipital regions, and decreased high-frequency (HF) and total HRV power. While the EEG changes are consistent with a more relaxed state, the HRV reductions could indicate a heightened autonomic arousal, suggesting that African stone could have triggered increased attention and physiological activation rather than merely relaxation. These findings demonstrate a divergence between subjective and physiological responses to scent exposure. Lavender appears to primarily reduce perceived anxiety, while African stone influences physiological arousal. We suggest that a multimodal approach be applied in aromatherapy research.